Fool, London/New York: Routledge, 2024. 81 p. Johanna Skibsrud - John Bengtsson Mayberry (Circus: Arts, Life & Sciences)
Review of: Skibsrud, Johanna (2024). Fool. London and New York: Routledge. The latest in the series, New Literary Theory. Editors Andy Mousley and Jeff Wallace.